Regulating hate speech on social media: should we or shouldn`t we? - Wan Mohd Nor, Murni; Ab Razak, Shahir (Malayan Law Journal, 2017)
Hate speech posted online is becoming a rising concern, particularly with the advancements in technology. Facebook, Twitter and other social media sites have been widely used as a medium for disseminating offensive, abusive and hateful content. There have been instances where such content has led to public outcry and even criminal prosecution. This article focuses on the issue of restricting hate speech on social media in Malaysia by examining online postings that offend racial and religious sensitivities; emphasising on the recent amendments to the Sedition Act 1948. It then considers the effects of these amendments on free speech and weighs them against the need to preserve peace and harmony within the community. The article concludes by arguing for the repeal of arbitrary restrictions that hinder our basic human rights to free speech and make recommendations as to what needs consideration if and when hate speech is specifically legislated against.